FEMALE RELIGIOSITY IN POST-SECULAR SOCIETY: ISLAM IN KAZAKHSTAN - BOLYSBAYEVA, Ainura; BOLYSBAYEVA, Aigerim; ZATOV, Kairat; TUTINOVA, Nurgul (CENTRAL ASIA AND THE CAUCASUS, 2021)
Today, religious renaissance across the post-Soviet space has moved into the center of academic attention mainly because post-Soviet countries have found themselves at the crest of religious awareness in the form of revived traditional religions. In Kazakhstan, this process has taken the form of Islamic revival, the religion of the autochthonous population, which lived in the territory of the contemporary state.According to many authors, the family is the main religious socialization institution: mothers as its main agents play the key role in raising the younger generation. This means that female religiosity requires close attention and detailed studies.With this aim in view, we carried out an online opinion poll among women 18 years and older in all regions of Kazakhstan to identify the interconnection between religious practices and involvement in religious life, on the one hand, and confessional self- identity, on the other, as well as the role of demographic statistical data (age, in particular) in shaping religious consciousness. We paid a lot of attention to the correlation between the degree of religiosity and the presence of Islamic dogmas in everyday life.Our studies brought us to a conclusion that the faithful generally tend to overestimate the extent of their religiosity. This means that the majority of our respondents can be described as conventional believers whose knowledge of the main Islamic dog- mas is weak and who do not observe religious practices. Religious holidays and fasting are the two most frequently observed practices; praying and religious clothes are the two frequently avoided practices. Their performance requires a lot of time and the need to change appearance and lifestyle.